The impact of Islamic based accounting education on professional conduct among accountants: a conceptual review - Nor Azah, Abdul Jalil; Hasnah, Haron; Muhammad, Muda (KnE Social Sciences, 2019)
The importance of developing a good curriculum for accountancy programs is due to the call of needs to ensure the safeguarding of the profession in the future. This paper tends to review the curriculum structure; emphasis on ethics and personal values (religiosity), which is presumed to have an impact on the conduct of accountants in their practice. Based on prior study, some ethics education programs have reported measurable success where it was found that ethics courses do improve students’ ability to recognize ethical issues and had a higher level of moral reasoning abilities after taking ethics courses. This review hopes to add value to the existing literature on perceptions of ethics and personal values impact for accountants’ behavior in their profession. Included in the review, are issued on the competency of the accountants.